The influence of iron deficiency on athletic performance – a narrative review - Malinowska, Marcelina; Bartela, Martyna (Quality in Sport, 2026)
Background: Iron deficiency represents one of the most prevalent nutritional disorders among athletes. Iron plays a crucial role in oxygen transport, energy production, and the proper functioning of muscles. A deficiency in iron can lead to a reduction in physical performance, an increase in fatigue, and complications in recovery. Objective of the Study: The primary objective of this research was to conduct an analysis of contemporary literature concerning the impact of iron deficiency on the physical performance of athletes. Additionally, the study aimed to discuss risk factors, diagnostic strategies, and potential supplementation options related to this issue. Materials and Methods: A narrative literature review was conducted encompassing the years 2015 to 2024. A comprehensive analysis was performed on review articles, clinical studies, and experimental research identified through the PubMed and Google Scholar databases. The selected publications focused on iron metabolism, exercise performance, and supplementation among physically active individuals. Results: Contemporary research indicates that iron deficiency can significantly affect aerobic capacity, increase the sensation of fatigue, and impair recovery. Endurance athletes and women are particularly vulnerable to this deficiency. Adequate diagnostic measures and the administration of supplements may enhance performance parameters and reduce the risk of decreased athletic endurance.